Biological characteristics and immune responses of NK Cells in commonly used experimental mouse models - Qin, Jingwen; Zhang, Zhaokai; Cui, Haopeng; Yang, Jinhua (Frontiers in Immunology, 2024)
The biology of natural killer (NK) cells in commonly used mouse models is discussed in this review, along with their crucial function in a variety of immunological responses. It has been demonstrated that the formation, maturation, subtype variety, and immunological recognition mechanisms of NK cells from various mice strains exhibit notable differences. These variations shed light on the intricacy of NK cell function and offer crucial information regarding their possible uses in treating human illnesses. The application of flow cytometry in mouse NK cell research is also covered in the article. Improved knowledge of the biology of NK cells across species may facilitate the development of new NK cell-based therapeutic approaches.